Una congettUra a Pseudo-Senofonte, Costituzione degli Ateniesi 2.17 - Luigi Battezzato (Exemplaria Classica, 2014)
The manuscript text of [X.] Ath. 2.17 gives impossible syntax and meaning: ?? ?? ?? ???????? ???? ?????????, †? ??’ ???? ??????†. The paper discusses previ- ous emendations, arguing that they are unsatisfactory, and conjectures that the original text was ?? ?? ?? ???????? ???? ?????????, ? ??’ ????? ??????? “in case they do not respect the agreements, or vio- late justice when under oath”.